The Effect of Project Based Learning on the Increase Students' Civic Knowledge Capabilities in the Digital Age - Maharani, Melina; Wuryandani, Wuri; Retnasari, Lisa; Wibowo, Setiawan Edi (Universitas Pendidikan Ganesha, 2024)
The low level of civic knowledge comprehension among students poses a challenge to learning processes aimed at fostering civic awareness and participation. This study aims to analyze the effect of Project-Based Learning (PjBL) on improving civic knowledge comprehension. The research employed an experimental research approach with a One Group Pretest-Posttest Design. The population consisted of 113 students, with a purposive sample of 51 students. Data were collected through validated tests designed to measure civic knowledge comprehension before and after the learning intervention. Data analysis was conducted using the n-gain test with the assistance of SPSS software to evaluate the effectiveness of the applied learning model. The results revealed that the implementation of PjBL significantly enhanced students' civic knowledge comprehension. A significant difference was observed between pretest and posttest scores, with a notable increase in average civic knowledge comprehension after the project-based learning intervention. These findings indicate that PjBL not only improves theoretical understanding but also supports the development of students' analytical and collaborative skills in addressing civic issues.